Why openness makes research infrastructure resilient. Issue 1 (18th January 2021) - Cousijn, Helena; Hendricks, Ginny; Meadows, Alice
Key points: Open research infrastructure provides the building blocks of scientific progress, which must be available to everyone, with no barriers to access. Organizations enabling open research infrastructure must endorse these fundamental principles: equity, value, trust, interoperability, sustainability, and community governance. Finding ways to invite co‐creation and community participation engenders a strong sense of 'buy‐in' and is therefore essential to developing successful research infrastructure.